2011
DOI: 10.1002/bdm.725
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Task Conflict to Group Decisions

Abstract: We tested the ability of task conflict to improve the quality of decisions made by four-person groups. In a choice between two entrepreneurial investments, conflict was created by endowing group members with a preference for either one investment or the other. Because the decision was subjective, decision quality was necessarily judged by a process criterion, the reduction in the biased evaluation of new information to support the leading alternative. Groups in which conflict was installed exhibited less bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Our research moreover complements other approaches to improve group decisions. For instance, assignment of expert roles (Stasser et al, ), creation of task conflict (Boyle, Hanlon, & Russo, ), and a group‐level counterfactual mindset (Liljenquist, Galinsky, & Kray, ) all have been shown to increase the impact of unshared information. These interventions, although effective by themselves, could be enhanced by adding implementation intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Our research moreover complements other approaches to improve group decisions. For instance, assignment of expert roles (Stasser et al, ), creation of task conflict (Boyle, Hanlon, & Russo, ), and a group‐level counterfactual mindset (Liljenquist, Galinsky, & Kray, ) all have been shown to increase the impact of unshared information. These interventions, although effective by themselves, could be enhanced by adding implementation intentions.…”
Section: Discussionmentioning
confidence: 99%
“…This has been accomplished in a study of group decision making. In the study, groups having members with different initial positions led to productive ‘task conflict’. That conflict prevented the emergence of a consistent leader, and thus the attendant leader‐driven ID.…”
Section: Guarding Against Information Distortionmentioning
confidence: 99%
“…In contrast, the teams of scenario writers will exhibit little or none of this distortion bias because the individuals in each team will successfully challenge each other's interpretations of the same drivers of the future. Boyle Hanlon and Russo (2012) found that when groups of four made a decision, there was no distortion bias so long as each of the two alternatives was favored (and defended) by at least one member of the group. However, as soon as the group agreed on a tentative leaning in favor of one alternative, the evaluation of new information became even more biased than for individuals working alone.…”
Section: Narrative Coherencementioning
confidence: 99%